PELATIHAN PEMBESARAN LOBSTER AIR TAWAR SISTEM SOLITER DI DESA SUNGAI KURUK, ACEH TAMIANG - Komariyah, Siti; Putriningtias, Andika; Alham, Fiddini; Azmi, Fauziah (Jurnal Abdi Insani, 2025)
The urgency of this community service activity is the need for efforts to improve the economy of partners, one of which is by providing skills to partners to carry out freshwater lobster (LAT) cultivation activities that have a high selling price. LAT cultivation was chosen as one of the strategies to improve the economy of partners because in addition to the high selling price, LAT is also easy to cultivate and does not require a large area of ​​land, so the community service team is sure that partners are able to carry out this LAT cultivation activity. The purpose of this activity is to provide skills to partners about LAT cultivation using gutters arranged like apartments so that the results of this LAT production can increase partner income. This community service activity is carried out in two stages, namely a pre-survey which aims to find out partner problems and discuss solutions and the implementation stage, namely socialization of LAT cultivation and training in assembling solitary system maintenance media using gutters. Based on the community service activities carried out in Muka Sungai Kuruk village, Aceh Tamiang, the participants were very enthusiastic about all the programs implemented by the team. In addition, partners also hope that there will be a continuation of this activity, namely training on LAT seeding.